Illegal Fishing by Other Countries: Complicated Law Enforcement in Indonesia - Febriyanto, Triyan; Setiaji, Mukhamad Luthfan (Universitas Negeri Semarang, 2022)
As an archipelagic country, illegal fishing become one of the challenges faced by Indonesia. This study aims to analyze the complexity of law enforcement in Indonesia in dealing with cases of illegal fishing carried out by other countries. This study confirms and finds that illegal fishing is illegal fishing activity or fishing activity carried out contrary to the provisions of laws and regulations in the field of fisheries. The government has also issued a number of regulations related to illegal fishing, including Law Number 31 of 2004 concerning Fisheries, Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries, Law Number 5 of 1983 concerning the Indonesian Exclusive Economic Zone, Law Number 21 of 2004 concerning Shipping, Law Number 6 of 1996 concerning Indonesian Waters, Presidential Regulation Number 115 of 2015 concerning the Task Force for the Eradication of Illegal Fishing, Minister of Maritime Affairs and Fisheries Regulation Number 37/Permen-KP/2017 concerning Standard Operational Enforcement Procedures Law of the Task Force for the Eradication of Illegal Fishing. This study also underlines that in Article 69 of Law Number 45 of 2009, fisheries surveillance vessels can stop, inspect, bring and detain vessels that are suspected or should be suspected of committing violations in the Indonesian fishery management area to the nearest port for further processing. Fishery investigators or supervisors can also take special action in the form of burning and/or sinking fishing boats with foreign flags based on sufficient preliminary evidence.